1999
DOI: 10.1021/bi990847b
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Controlling the Membrane Binding of Basic Protein Domains:  Phenylalanine and the Attachment of the Myristoylated Alanine-Rich C-Kinase Substrate Protein to Interfaces

Abstract: Basic residues are known to play a critical role in the attachment of protein domains to membrane interfaces. Many of these domains also contain hydrophobic residues that may alter the binding and the position of the domain on the interface. In the present study, the role of phenylanine in determining the membrane position, dynamics and free energy of a peptide derived from the effector domain of the myristoylated alanine-rich C-kinase substrate (MARCKS) protein was examined. Deuterium NMR in membranes contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
67
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 32 publications
12
67
1
Order By: Relevance
“…2A shows that FA-MARCKS (‚) binds 100-fold less strongly to 99:1 PC/PIP 2 vesicles than MARCKS-(151-175) (E). The observation that the 5 Phe residues contribute significantly (ϳ3 kcal/mol) to the binding energy is consistent with previous observations that the Phe residues of MARCKS-(151-175) penetrate the polar head group region of the membrane (40,45,72). The aromatic residues contribute to the binding of MARCKS-(151-175) not only to PC/PIP 2 vesicles but also to PC/PS vesicles.…”
Section: The Binding Of Truncated Marcks-(151-175) Peptides To Pc/pipsupporting
confidence: 90%
“…2A shows that FA-MARCKS (‚) binds 100-fold less strongly to 99:1 PC/PIP 2 vesicles than MARCKS-(151-175) (E). The observation that the 5 Phe residues contribute significantly (ϳ3 kcal/mol) to the binding energy is consistent with previous observations that the Phe residues of MARCKS-(151-175) penetrate the polar head group region of the membrane (40,45,72). The aromatic residues contribute to the binding of MARCKS-(151-175) not only to PC/PIP 2 vesicles but also to PC/PS vesicles.…”
Section: The Binding Of Truncated Marcks-(151-175) Peptides To Pc/pipsupporting
confidence: 90%
“…residues within the effector domain and negatively charged phospholipids and via a penetration of the phenylalanine side chains within the effector domain into the lipid bilayer (33,34). Similar to MARCKS, it has been shown that PSA associates with liposomal membranes and penetrates lipid bilayers (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that PSA at least partially triggers signal transduction via an interaction with MARCKS at the plasma membrane and that this interaction interferes with PKC-dependent signal transduction. (33,34). Exchanging the serine residues in the effector domain to alanine, asparagine, or aspartic acid or mutation of the myristoylation site prevents the membrane insertion of MARCKS (28).…”
Section: Psa Directly Binds To the Effector Domain Of Marcks-mentioning
confidence: 99%
“…EPR spectroscopy (17) and circular dichroism (13) have shown that this peptide adopts an extended conformation when bound to membrane bilayers. Cafiso and co-workers (18,19) have undertaken an extensive series of EPR studies on MARCKS-(151-175) to probe its location relative to the membrane surface. They systematically substituted amino acids in the MARCKS-(151-175) sequence with cysteines derivatized with nitroxide spin labels and found that spin labels attached at the highly basic and hydrophilic N and C termini of the peptide reside on the aqueous side of the lipid phosphate head group, whereas spin labels attached to the central Phe-containing portions of the peptide are located several angstroms below the lipid head group (17).…”
mentioning
confidence: 99%